A novel missense mutation of FOXC1 in an Axenfeld-Rieger syndrome patient with a congenital atrial septal defect and sublingual cyst: a case report and literature review - Kaiming Li; Min Tang; Manhua Xu; Yinggui Yu (BMC, 2021)
Abstract Background Axenfeld-Rieger syndrome (ARS) is a rare autosomal dominant hereditary disease characterized primarily by maldevelopment of the anterior segment of both eyes, accompanied by developmental glaucoma, and other congenital anomalies. FOXC1 and PITX2 genes play important roles in the development of ARS. Case presentation The present report describes a 7-year-old boy with iris dysplasia, displaced pupils, and congenital glaucoma in both eyes. The patient presented with a congenital atrial septal defect and sublingual cyst. The patient's family has no clinical manifestations. Next generation sequencing identified a pathogenic heterozygous missense variant in FOXC1 gene (NM_001453:c. 246C>A, p. S82R) in the patient. Sanger sequencing confirmed this result, and this mutation was not detected in the other three family members. Conclusion To the best of our knowledge, the results of our study reveal a novel mutation in the FOXC1 gene associated with ARS.